2020
DOI: 10.1097/cad.0000000000000975
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated long noncoding RNAs LINC02163 and FEZF1-AS1 exert oncogenic roles in colorectal cancer

Abstract: A growing number of evidence has revealed that aberrantly expressed long noncoding RNAs (lncRNAs) are involved in the development of a variety of malignancies, including colorectal cancer (CRC). However, the clinical relevance of most lncRNAs and their potential biological functions in CRC remains poorly understood. The aim of this study was to identify the key lncRNAs related to patient prognosis as well as their biological function and underlying mechanism in CRC. Therefore, five independent datasets contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Among the six lncRNAs in the prognostic model, LINC02163 and CASC9 were found to be upregulated in various cancers including HCC. LINC02163 and CASC9 were closely associated with the patient’s survival and acted as a candidate prognostic biomarker with their significant values ( Dong et al, 2018 ; Qin et al, 2020 ; Qi et al, 2021 ; Tian et al, 2021 ). LINC02362 and AC008549.1 were identified to be tumor-inhibitory lncRNAs and contributed to the patient’s survival of HCC, while the lncRNA AC008549.1 was classified as a pyroptosis-related signature ( Wang et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the six lncRNAs in the prognostic model, LINC02163 and CASC9 were found to be upregulated in various cancers including HCC. LINC02163 and CASC9 were closely associated with the patient’s survival and acted as a candidate prognostic biomarker with their significant values ( Dong et al, 2018 ; Qin et al, 2020 ; Qi et al, 2021 ; Tian et al, 2021 ). LINC02362 and AC008549.1 were identified to be tumor-inhibitory lncRNAs and contributed to the patient’s survival of HCC, while the lncRNA AC008549.1 was classified as a pyroptosis-related signature ( Wang et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A series of functional experiments in vitro and in vivo have validated the oncogenic property of FOXD3-AS1 in colon cancer through of the regulation of cell proliferation, migration, invasion, and apoptosis. However, Tian Y et al has also demonstrated that low expression of FOXD3-AS1 in colon cancer patients is associated with worse overall survival (93). Therefore, more research is needed to clarify the specific role of FOXD3-AS1 in colon cancer.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…(J) Linc02163: Among other lincRNAs found to be deregulated in cancer, Linc02163 was recently shown to play a role in colorectal and breast cancer [ 76 , 77 ]. Linc02163 is located on chromosome 5q21.2 and it was found to be upregulated in breast cancer tissues compared to adjacent normal tissues with the findings being verified in four different breast cancer cell lines (SKBR3, MDA-MB-231, MCF-7, and BT-474) as compared to human immortalized breast epithelial cell line MCF-10A [ 77 ].…”
Section: Introductionmentioning
confidence: 99%